Toxic Parenting dan Dampaknya terhadap Kemerosotan Moral Anak - Fauziah, Riska; Kamaliyah, Mawritsa; Azzahra, Hanifah (Tadabbur: Jurnal Integrasi Keilmuan, 2024)
The purpose of the study was to determine the characteristics of toxic parenting towards children in the family. This study was motivated by the parenting patterns of parents towards their children. Parenting patterns are habits that parents do to their children such as caring for, guiding and leading their children in the family. However, this is not the case with toxic parenting, this toxic parenting pattern parents will treat their children badly, for example, controlling their children too much, like shouting at children, committing verbal violence, blaming children, criticizing and being selfish with the aim of the good of their children. However, in reality, this condition will make children depressed, stressed, stressed, and not confident. The method used is descriptive analysis. Based on the results of research on toxic parenting, it can be concluded that toxic parenting is very dangerous and has a major negative effect on children's development in the future. This is because parenting patterns like this have a chain that will later be carried out by the child when they are adults and have children, because they assume that the parenting patterns carried out by their parents are good. To avoid toxic parenting, parents must try to understand their children's behavior, provide opportunities for children, control emotions and establish good communication with children.